Chemoselective Hydrogenation of Aromatic Nitro Compounds Using Diammonium Hydrogen Phosphite and Commercial Zinc Dust - K. Anil Kumar; K. S. Shruthi; Nagaraja Naik; D. Channe Gowda (E-Journal of Chemistry)
The aromatic nitro compounds are reduced to their corresponding amines at room temperature in good yields by employing diammonium hydrogen phosphite as hydrogen donor and zinc as catalyst. The hydrogenation is fast and selective in the presence of the other sensitive functionalities such as halogens, -OH, -NH2, -OCH3, -CN, -COCH3, -COOH, -COOR etc. It was observed that, this system is equally competitive with existing methods.